Pulse-amplitude equalization in the monotonic region of the modulator of a rational-harmonically mode-locked fiber ring laser - Moon, Byunghyuck; Kim, Yong Soo; Ju, Byeong-Kwon; Lee, Ju Han; Jhon, Young Min (IOP PUBLISHING LTD, 2020)
We investigate characteristics of the modulator and classify the modulation regions to study pulse-amplitude equalization (PAE) of a rational-harmonically mode-locked fiber ring laser pulses. PAE was accomplished experimentally in a polarization-maintaining laser resonator simply by optimizing the modulator driving power without any additional devices, and stable pulse-amplitude-equalized pulses were obtained in the monotonic region of the modulator at repetition rates of 20 GH, 30 GH, and 40 GH.
Keywords: LOCKING; GENERATION